Factors associated with dropout in a self-guided transdiagnostic intervention for a Mexican population - Hernandez-Orduña, Omar (2025)
Background: Technology has revolutionized mental health, enabling access to diverse and more accessible therapies. Telepsychology interventions, such as self-guided ones, offer personalized treatments through digital platforms. Although long-term studies are limited, these approaches have shown effectiveness in various disorders. Modality and the specific disorder influence the effectiveness of these therapies. Understanding and identifying factors that influence the abandonment of self-guided treatments is crucial to improving their design and increasing the likelihood of their completion. Objective: This study seeks to identify factors that influence the abandonment of self-guided treatments for emotional problems related to stress and trauma. With this, it is possible to include tools that improve the effectiveness of these treatments. Methods: The sample included 89 adults evaluated through diagnostic interviews, who met criteria for emotional or stress-related disorders and were assigned to a self-guided transdiagnostic treatment with eight modules that could be accessed at any time. Results: A dropout rate of 81% of participants was identified, mainly during the first sessions. Through logistic regression analysis, some significant factors for abandonment were identified, such as place of residence and anxiety levels. Conclusion: Strategies such as personalized reminders, continuous clarification of treatment objectives, and tools that drive patient motivation towards treatment could prevent abandonment. The results offer valuable information for optimizing telepsychology and ensuring success in self-guided psychological treatments in diverse technological and cultural contexts.